The Six Great Societies. Issue 2 (13th May 2016) - Hackett, Ursula
Abstract : "The Great Society" denotes, variously: a slogan or shorthand, a utopia, a means, an end, an era, and a set of normative claims. This article tracks the changing meanings of The Great Society in order to clarify and formalize scholarly claims about the Johnson administration. Employing Edward Sapir's conception of "condensation symbols" and Keith Donnellan's distinction between "referential" and "attributive" descriptions, I create a typology of six Great Societies and trace the origins and deployment of these six meanings through qualitative textual analysis of presidential speeches, newspapers, and scholarly writings. Attributive uses of the term gave way to referential uses in the late 1960s, as radical movements and practical implementation problems eclipsed utopian visions of a great society. The analysis illuminates Johnson's character and contributes to the literature on the rhetorical presidency by demonstrating the importance of context, ambiguity, and the attribution of descriptive content to political slogans.